Demographic and functional determinants of large-scale population dynamics and ecological niches of 26 serotinous Proteaceae - Treurnicht, Martina (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhDAgric)--Stellenbosch University, 2018.